β-Ionone Treatment Enhances the Antioxidant Capacity in Postharvest Broccoli (Brassica oleracea L. var. Italica) by Maintaining the Levels of Bioactive Substances - Feng Zhang; Mengze Cao; Letong Shen; Liyu Shi; Wei Chen; Zhenfeng Yang (Foods)
Broccoli is prone to nutrient loss during postharvest storage due to its high respiratory metabolism. In this study, we investigated the effects of 0.1 mm β-ionone on bioactive substances and antioxidant capacity during postharvest storage of broccoli. We found that the decline in the scavenging rates of 1,1-diphenyl-2-picrylhydrazyl and 2,2′-azinobis-(3-ethylbenzthiazoline-6-sulphonate) radicals was delayed in the treated florets. This delay is attributed to β-ionone treatment, which upregulated the expression of biosynthetic genes related to glucosinolates and riboflavin in broccoli, thereby slowing the loss of these nutrients. Additionally, β-ionone treatment increased the transcript levels of anabolic genes while reducing the expression of genes encoding enzymes involved in the catabolism of ascorbic acid (AsA) and glutathione (GSH), resulting in higher levels of AsA and GSH in treated broccoli compared to the control. Overall, β-ionone treatment enhanced antioxidant capacity by delaying the loss of bioactive substances in postharvest broccoli. These findings provide the first evidence that exogenous β-ionone helps preserve antioxidant capacity in postharvest horticultural products.